PENGARUH TEKNIK JARIMATIKA TERHADAP HASIL BELAJAR MATEMATIKA MATERI PENJUMLAHAN DAN PERKALIAN 1-10 - Tika Hardianti; Atiaturrahmaniah Atiaturrahmaniah; Muh. Yazid (Program Studi PGSD Universitas Flores, 2021)
This study aims to determine the effect of Jarimatika techniques on learning outcomes in mathematics with the material of addition and multiplication of 1-10. The design used in this study was the one-group pretest-posttest design. In this design, there is one group or class being studie. In this design the effect or effect of a treatment is seen based on the results of the posttest and pretest. The subjects of this study were 22 students of Class II SDN 5 Dasan Lekong. To measure the learning outcomes of students used tests (short answers). For the prerequisite test, the data normality test was performed using the chi square formula. From the test results, data is normally distributed. While testing the hypothesis using the t-test formula. Based on the results of the posttest, the average score was 77.4, while the pretest was 67.1. For the hypothesis test results obtained tcount> ttable, namely 5.358> 2.018. This means that the accepted hypothesis is that there is an effect of the technique on the mathematics learning outcomes of the addition and multiplication material of 1-10 grade II SDN 5 Dasan Lekong students in the 2020/2021 school year.